KEPRIBADIAN PENDIDIK MUSLIM - Firdaus Syah (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Educator is a very honorable and noble job, because the main task for an educator is not just teaching but more than that, which is guiding students to become human beings who are especially useful for themselves, their families, and society in general. The caracteristics of the Muslim personality is the realization of noble behavior in accordance with the guidance of the Qur'an and Hadith, which in other terms is called noble character. In the context of Islamic education, educators are called murabbi, mualilim, muaddib, mudarris, muzakki and ustadz. Educators in Islamic education are Allah SWT, Rasulullah SAW, parents and teachers. In order for an educator to carry out the functions that Allah has assigned to the Prophet and his followers, he must have a rabbaniyah personality and character in his goals and behavior as well as his mindset.